The idea of Eurasianism in Russia (Journal of actual problems of jurisprudence, 2018)
The article deals with the Eurasian idea Russia. The political concept developed in the first quarter of the twentieth century. The core of the concept of emigration from Russia after the revolution and a common understanding by bringing the concept of national values set mode. However, there werea changesover time, on the concept of Eurasianism. Today, Russia uses to protect its interests the Eurasian idea. Russia’s state-supportan idea of the special mission as the core of the idea is to protect the benefits because it has become a part of the imperialist idea.Key words: Eurasianism, empire, east, imperialism.